On the connection between the stability of multidimensional positive systems and the stability of switched positive systems - Paula Rocha (2017)
In this work, we study the connection of the stability of multidimensional positive systems with the stability of switched positive systems. In a previous work, we showed that the stability of a multidimensional positive system implies the stability of a related switched positive system. Here, we investigate the reciprocal implication. (c) Springer International Publishing AG 2017.